2016
DOI: 10.1108/nfs-10-2014-0091
|View full text |Cite
|
Sign up to set email alerts
|

Relation between probiotic properties of isolates isolated from breast milk and infants’ stools

Abstract: Purpose Breast milk has been hypothesized to be a source of bacteria for the infant gut. This paper aims to search for probiotic bacteria among 415 isolates belonging to the Enterococcus, Lactobacillus, Streptococcus and Bifidobacterium genera recovered from breast milk of 50 lactating mothers and their respective infant stools, and then, determine whether their levels in stools vary with different modalities of breast feeding. Design/methodology/approach To prove that the isolates were probable probiotics, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…They compete with pathogenic bacteria for nutrients and colonize GIT effectively (38). Moreover, several studies have reported new probiotics from feces of breast-fed infant since they are dominated by bifidobacteria, lactobacilli, enterococci, and other LABs (23,(39)(40)(41). In this study, nine E. faecalis strains, PK1003, PK1201, PK1202, PK1301, PK1302, PK180, PK2003, PK2004, and PK2502, were isolated from the feces of breastfed infants for their potent tolerance toward GIT conditions.…”
Section: Discussionmentioning
confidence: 99%
“…They compete with pathogenic bacteria for nutrients and colonize GIT effectively (38). Moreover, several studies have reported new probiotics from feces of breast-fed infant since they are dominated by bifidobacteria, lactobacilli, enterococci, and other LABs (23,(39)(40)(41). In this study, nine E. faecalis strains, PK1003, PK1201, PK1202, PK1301, PK1302, PK180, PK2003, PK2004, and PK2502, were isolated from the feces of breastfed infants for their potent tolerance toward GIT conditions.…”
Section: Discussionmentioning
confidence: 99%